(untitled) (ABUJA JOURNAL OF BUSINESS AND MANAGEMENT, 2025)
Small and medium-scale enterprises play a crucial role in fostering economic development, innovation, and employment generation in Nigeria. In Abuja, SMEs significantly contribute to local economic growth and provide livelihoods for many individuals. However, their ability to compete in an increasingly digitalized and dynamic marketplace remains a major challenge. This study examined data analytics and competitiveness of SMEs in FCT, Abuja. The study adopted a descriptive research design in which simple random Sampling was used to obtain data from the respondents with the questionnaire administered to the employees and managers from SMEs across six area councils: Abuja Municipal, Gwagwalada, Kuje, Bwari, Abaji, and Kwali, with a population of 553 selected employees and managers from SMEs across six area councils: Abuja Municipal, Gwagwalada, Kuje, Bwari, Abaji, and Kwali were targeted. Cluster Sampling was used while sample size (232) was used with a 20% margin of safety added to the sample size making it 278. The data were analyzed using inferential statistics and regression analysis at a 5% level of significance to test the formulated hypotheses in line with the objectives of the study. The findings revealed the adoption of data analytics tools significantly affects the operational efficiency and market responsiveness of SMEs in FCT, Abuja. The research concludes that the adoption of data analytics tools significantly affects the operational efficiency and market responsiveness of SMEs in FCT, Abuja. The study recommended that SMEs in FCT, Abuja, should prioritize investment in modern data analytics tools to enhance decision-making, improve efficiency, and gain a competitive advantage.